South African employees’ perceptions - Knowles, Tanya (My University, 2011)
The aim of this study was to look at the topic of leadership from an employee’s perspective by establishing the extent to which employees’ have a common perception of an effective leader in business. The study aimed to uncovered whether employees’ perceptions of an effective leader varied in relation to their level of seniority in an organisation. This was undertaken within the context of a transactional and transformational leadership framework. A questionnaire administered to employees across industries in South Africa was used as a basis for the study. The sample consisted of 142 respondents and each respondent was requested to rate their perceptions of effective leadership in business. The researcher administered an adapted Multifactor Leadership Questionnaire (MLQ) questionnaire to respondents which was designed and validated by Avolio and Bass (1995) to measure transactional and transformational leadership. The statistical measures used in the study included descriptive statistics and analysis of variance (ANOVA) tests. The study showed that overall employee’s perceptions of effective leadership, when assessed within the transactional and transformational leadership framework, did not significantly differ based on their level of seniority within an organisation. The results indicated that while employees overall, perceive an effective leader to display a higher degree of transformational leadership than transactional leadership. An exception was identified relating to the transactional dimension of Contingent Reward. Although Contingent Reward falls within the dimension of transactional leadership, it was rated by respondents as having equal weighting to the dimensions of transformational leadership. v The research has shown that the application of the theories of transactional and transformational leadership can be more broadly applied for leaders dealing with subordinates at various levels of an organisation. An employee’s level of seniority within an organisation does not impact their perception of effective transactional leadership, however, the research revealed that an employee’s level of seniority within an organisation impacts their perception of effective transactional leadership at a top / senior management level when compared to professionally qualified / middle management, skilled / junior management and semi-skilled staff. Top / senior management are seen to be aware of the importance of transformational leadership from a strategic level where they set the strategic direction for the organisations and are responsible for the achievement thereof. This ultimately should lead to increased employee satisfaction, sustained organisational performance and a fair return to shareholders
MBA - WBS
Keywords: Leadership; Transformational leadership; Transactional leadership; Employees